2018
DOI: 10.3847/1538-4365/aab77f
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Solar Eruptions Using Filament Metadata

Abstract: We perform a statistical analysis of erupting and non-erupting solar filaments to determine the properties related to the eruption potential. In order to perform this study, we correlate filament eruptions documented in the Heliophysics Event Knowledgebase (HEK) with HEK filaments that have been grouped together using a spatiotemporal tracking algorithm. The HEK provides metadata about each filament instance, including values for length, area, tilt, and chirality. We add additional metadata properties such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Wang et al, 2003;Veronig et al, 2006b;Vršnak et al, 2006b;Miklenic et al, 2007;Pötzi et al, 2015;Thalmann et al, 2015;Joshi et al, 2017;Temmer et al, 2017;Hinterreiter et al, 2018;Tschernitz et al, 2018), filament eruptions and dynamics (e.g. Maričić et al, 2004;Möstl et al, 2009;Zuccarello et al, 2012;Su et al, 2012;Filippov, 2013;Yardley et al, 2016;Aggarwal et al, 2018), Moreton waves (e.g. Pohjolainen et al, 2001;Warmuth et al, 2001;Vršnak et al, 2006a;Veronig et al, 2006a), as well as for long-term evolution of the distributions of prominences and polar crown filaments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al, 2003;Veronig et al, 2006b;Vršnak et al, 2006b;Miklenic et al, 2007;Pötzi et al, 2015;Thalmann et al, 2015;Joshi et al, 2017;Temmer et al, 2017;Hinterreiter et al, 2018;Tschernitz et al, 2018), filament eruptions and dynamics (e.g. Maričić et al, 2004;Möstl et al, 2009;Zuccarello et al, 2012;Su et al, 2012;Filippov, 2013;Yardley et al, 2016;Aggarwal et al, 2018), Moreton waves (e.g. Pohjolainen et al, 2001;Warmuth et al, 2001;Vršnak et al, 2006a;Veronig et al, 2006a), as well as for long-term evolution of the distributions of prominences and polar crown filaments (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yu et al (2009) and Yuan et al (2010) used line-of-sight magnetogram data obtained from Michelson Doppler Imager (MDI) for flare prediction. Aggarwal et al (2018) used filament metadata for the prediction of eruptive events. However, most of the studies used vector magnetogram data obtained from the Helioseismic Magnetic Imager (HMI) onboard the Solar Dynamics Observatory (SDO) for the purpose of flare prediction.…”
Section: Introductionmentioning
confidence: 99%
“…McCauley et al (2015) studied the kinematics of more than one hundred limb prominence eruptions and found that the decay index at the onset of the fast-rise is in the range 0.7-2 with a mean value of n c  1.1. The average decay index for eruptive filaments in 2012 --2013 in the study of Aggarwal et al (2018) has fairly broad distributions in the range 0 --2, with a mean value of 0.84. Sarkar et al (2019) found that before the eruption on 2010 June 13 the top of a polar crown prominence reached the height with the decay index value of 1.2, while the decay-index value at the corresponding cavity centroid height reached the critical limit of 1.4 for the onset of torus instability.…”
Section: Introductionmentioning
confidence: 89%